Implementation of Total Quality Management (TQM) in Enhancing School Competitiveness in the Era of Disruption - Putri Rosana; Vebby Andra; Heny Friantary (JMiE (Journal of Management in Education), 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving school competitiveness in the disruption era. The research employed a qualitative approach through literature review and case studies in educational institutions. Data were collected through observations, in-depth interviews with school stakeholders, and documentation related to quality management policies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings revealed that effective TQM implementation is supported by five main dimensions: adaptive transformational leadership, customer satisfaction orientation, continuous data-based improvement, full involvement of human resources, and the utilization of information technology in quality management. Schools that consistently implemented TQM demonstrated improvements in accreditation, student achievement, institutional reputation, and public trust. The study concludes that the integration of TQM and technological innovation contributes to adaptive, effective, and sustainable school management in responding to the challenges of the disruption era.